Research on Operating Condition Effect on the Shock Pulse Method - Ruifeng Zhang; Jianshe Kang; Lishan Hao; Xinghui Zhang; Hongzhi Teng; Haiping Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Rolling bearings are one of the most widely used elements in industrial applications. Shock pulse method (SPM) has proven successfully as a diagnostic tool in determining bearing health. On the basis of illustrating the principle of SPM, this paper mainly concentrates on investigating the effect of different operating conditions on SPM. The shock pulse signals are derived from the wind turbine gearbox test rig by SPM instrument. Through comparing the slope of dB values when the rotating speed or load changes, effect of operating conditions on SPM is analyzed. The analysis results show that SPM is more sensitive to the rotating speed in contrast with the load.